Minds on stage: Greek tragedy and cognition - Budelmann, Felix; Sluiter, Ineke (Cognitive classics, 2023)
'Minds on Stage' expands our understanding of Greek tragedy, and uses Greek tragedy as a way to explore cognitive thinking. We see both 'minds on stage', understanding and dealing with complex situations and with each other, and 'minds in the audience', following the action, forming a picture of the characters' inner worlds.